Comparative study on treatment of acute cerebral infarction between mechanical thrombectomy by micro catheter and thrombectomy by Solitaire AB stent - Xiaoli Dong, MM; Guodong Xu, MD; Yaxue Song, MM; Liang Ma, MM; Tiantian Huo, MM; Nan Yin, MD; Nan Meng, MM; Ahmed Salah Naser. (Medicine, 2022)
Abstract. Background:. Acute cerebral artery occlusion is a common disease with high morbidity and mortality. At present, the commonly used mechanical thrombectomy schemes are mechanical thrombectomy and stent thrombectomy. However, the clinical differences between the two methods is not fully understood. The present study aimed to evaluate the clinical effectiveness of Solitaire AB stent thrombectomy for acute cerebral infarction (ACI). Methods:. A retrospective study was carried out in 96 ACI patients admitted to our department from January 2017 to January 2020. According to the treatment they received, they were divided into group A (conventional microcatheter mechanical thrombectomy, n = 48) and group B (Solitaire AB stent thrombectomy, n = 48). All patients were followed up for 3 months. Their pre- and post-operative nerve function indices were compared between the 2 groups. The therapeutic effects were evaluated by thrombolysis in cerebral infarction scale system, Glasgow coma scale (GCS), National Institutes of Health Stroke Scale (NIHSS), and modified Rankin scale statistics. Results:. Two groups of patients with NIHSS scores postoperative 3 and 30 days decreased significantly compared with preoperation. NIHSS score of group A 3 and 30 days postoperation was significantly higher than group B (P < .05). Two groups of patients with GCS scores postoperative 3 and 30 days increased significantly compared with preoperation. GCS score of group A 3 and 30 days postoperation was significantly lower than group B (P < .05). Group B with vascular recanalization ratio postoperative 30 days was higher than group A, however with no significant differences (P > .05). Moreover, group B with outcomes (modified Rankin scale score ≤2 points) postoperative 3 months was better than group A, however with no significant differences (P > .05). Conclusion:. Solitaire AB stent embolectomy shows similar efficacy as mechanical thrombectomy in the treatment of ACI patients.